A renewed approach to the foundations of SIA theory: generalizing SIA to incorporate multiple behavior hypotheses. Thoughts on the implicative intensityUne approche renouvelée des fondements de l’ASI : Une généralisation de l’ASI - Delacroix, Thomas (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2014)
The aim of this paper is to recall the foundations of SIA theory and modify these slightly in order to clarify and reinforce them, as well as make them more adaptable to various scientific models. Some issues regarding one of the founding blocks of SIA, the implicative intensity, are discussed and detailed. This paper is composed of two mostly separable sections. The first half of this paper focuses on a generalization of SIA so that known differences between individuals, which we shall refer to as multiple behaviors, can be taken into account in an analysis. The second half focuses on two issues related to the implicative intensity, the second of which being the well-known issue raised by large numbers of individuals in SIA data sets. On souhaite ici rappeler les fondements de l’ASI et les modifier légèrement de manière à clarifier certains points et à les renforcer, ainsi qu’à les rendre plus adaptables à différentes modélisations scientifiques. Des questions soulevées concernant l’un des piliers de l’ASI, l’intensité d’implication, sont discutées et détaillées. L’article est articulé autour de deux parties relativement dissociables. La première partie concerne une généralisation de l’ASI permettant de prendre en compte dans les analyses des différences connues entre individus qui seront désignées par le terme de comportements multiples. La seconde partie concerne deux questions soulevées relatives à l’intensité d’implication, en particulier la question bien connue en ASI des difficultés d’analyse pour des données portant sur un grand nombre d’individus.